Views of Sociology of Law Regarding Community Social Control - Murdoko; Rossita Trijaya Novia; Edi Prianto; Vicki Dwi Purnomo (PT FORMOSA CENDEKIA GLOBAL, 2023)
Law plays an active role as something that can determine human behavior that deviates from the rule of law. The cause of the law not working well is due to low public awareness of the law itself. Legal causes are irrelevant to the reality of society because existing laws are formed from the will of the elite (rulers), while society is the target object. In fact, in order for the law to apply responsively, the law must be formed from the realities that live in society. The results of the study can be concluded that the use of a sociological perspective in analyzing legal issues (legal sociology), namely: sociology of law is useful to provide the ability to understand law in a social context, mastery of the concepts of sociology of law can provide the ability to conduct an analysis of the effectiveness of law in society, both as a means of social control, a means of changing society and a means of regulating social interaction, in order to achieve certain social conditions, and provide the ability to evaluate the effectiveness of law in society.